Cancer Risks for MLH1 and MSH2 Mutation Carriers. Issue 3 (18th February 2013) - Dowty, James G.; Win, Aung K.; Buchanan, Daniel D.; Lindor, Noralane M.; Macrae, Finlay A.; Clendenning, Mark; Antill, Yoland C.; Thibodeau, Stephen N.; Casey, Graham; Gallinger, Steve; Marchand, Loic Le; Newcomb, Polly A.; et al.
<x xml:space="preserve">Abstract</x> Our estimates of colorectal and endometrial cancer risks for MLH1 and MSH2 mutation carriers are the most precise currently available. Average risks are similar for the two genes but there is so much individual variation about the average that a sizeable proportion of carries are almost certain to develop cancer whereas another sizeable proportion only have population‐level risks. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>